2019
DOI: 10.3390/en12101984
|View full text |Cite
|
Sign up to set email alerts
|

A General Transformer Evaluation Method for Common-Mode Noise Behavior

Abstract: In isolated power converters, the transformer is a key part of voltage transformation and isolation. Since common-mode (CM) noise is rather difficult to suppress compared with different-mode (DM) noise, more and more scholars are paying attention to the characteristics of CM noise, especially in high-frequency CM noise behaviors. CM noise can be further divided into conducted CM noise and radiated CM noise, and the main focus of this paper is on conducted CM noise. The CM coupling capacitance of the transforme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
0
0
0
Order By: Relevance
“…In the case of high-frequency isolation, the important point is the existence of a stray parasitic capacitor between the primary and secondary of the high-frequency transformer C iW (interwinding capacitor). In different studies, different methods have been presented to model this capacitor, which is in the picofarad range [67,68]. Stray capacitors in parallel to insulation resistance are used here for a high-frequency transformer.…”
Section: Isolated Casementioning
confidence: 99%
“…In the case of high-frequency isolation, the important point is the existence of a stray parasitic capacitor between the primary and secondary of the high-frequency transformer C iW (interwinding capacitor). In different studies, different methods have been presented to model this capacitor, which is in the picofarad range [67,68]. Stray capacitors in parallel to insulation resistance are used here for a high-frequency transformer.…”
Section: Isolated Casementioning
confidence: 99%
“…Reference [16] utilized core shielding to address the coupling problem caused by the transformer core and employed a converter to solve the issues of multi-Y capacitance and capacitive filtering, providing better EMI suppression compared to conventional pulse-width modulation. Reference [17] highlighted the significant influence of transformer common-mode coupling capacitance on noise suppression and demonstrated that the feasibility of the transformer can be verified without an EMI receiver, using only a signal generator and an oscilloscope. References [18][19][20] incorporated balanced winding techniques to achieve effective shielding and offset common-mode noise, and they provided a theoretical method for calculating the number of turns in a balanced winding, which is valuable for this study.…”
Section: Introductionmentioning
confidence: 99%